A Fractal Universe and the Identity of Indiscernibles - Casarosa, Matteo (Stance: an international undergraduate philosophy journal, 2019)
The principle of Identity of Indiscernibles has been challenged with various thought experiments involving symmetric universes. In this paper, I describe a fractal universe and argue that, while it is not a symmetric universe in the classical sense, under the assumption of a relational theory of space it nonetheless contains a set of objects indiscernible by pure properties alone. I then argue that the argument against the principle from this new thought experiment resists better than those from classical symmetric universes three main objections put forth against this kind of arguments.